How Does Financial Market Development Influence Environmental Sustainability in Saudi Arabia? - Bin Salman, Abdulrahman Khalid; Oueslati , Tarek; Missaoui, Ibtissem (International Journal of Energy Economics and Policy, 2026)
The integration of environmental and sustainability goals within Saudi Arabia’s financial regulatory framework has received significant attention to enhance green finance initiatives aligned with Vision 2030. By using the ARDL method with FMOLS, DOLS, and CCR estimators, this study investigates the impact of market-based financial development (FMD), GDP per capita (GDP), energy consumption per capita (ENG), and trade openness (TO) on the overall greenhouse gas emissions of Saudi Arabia (EQ) between 1994 and 2020. Our results indicate that financial development and energy consumption are significant contributors to emissions, as per the carbon content of energy and industrial investment. Also, GDP per capita has a positive effect, and trade openness serves as a moderator, reducing emissions over the long term. Short-run dynamics exhibit rapid convergence to the long-run equilibrium as captured in the negative in statistically significant error-correction coefficient. Based on these results, the Saudi government should encourage financial development management, promote energy efficiency, and utilize trade policies, as these factors are significant for reducing emissions and maintaining sustainable environmental performance in Saudi Arabia.